2016
DOI: 10.2337/db16-0020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Induces Keap1 S-sulfhydration and Suppresses Diabetes-Accelerated Atherosclerosis via Nrf2 Activation

Abstract: Hydrogen sulfide (H2S) has been shown to have powerful antioxidative and anti-inflammatory properties that can regulate multiple cardiovascular functions. However, its precise role in diabetes-accelerated atherosclerosis remains unclear. We report here that H2S reduced aortic atherosclerotic plaque formation with reduction in superoxide (O2−) generation and the adhesion molecules in streptozotocin (STZ)-induced LDLr−/− mice but not in LDLr−/−Nrf2−/− mice. In vitro, H2S inhibited foam cell formation, decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
206
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(216 citation statements)
references
References 35 publications
9
206
1
Order By: Relevance
“…2 HG-induced reactive oxygen/nitrogen species (ROS/RNS) overproduction may be a key event in activation of signaling pathways involved in the pathogenesis of atherosclerosis. 2,3 Interestingly, the mechanism of autoxidation describes the capability of glucose to enolize, thereby reducing molecular oxygen and yielding oxidizing intermediates, including superoxide anion (O 2 When macrophages respond to HG, ROS/RNS production was increased in cellular compartments and these reactive species triggered DNA strand breakage, leading to rapid increase in amounts of 8-hydroxydeoxyguanosine in DNA and decreases in the amount of DNA repair enzyme 8-oxoguanine glycosylase (OGG1). 2 Recent studies have revealed that HG-induced cellular changes lead to alterations of signal transduction cascades in macrophages, affecting gene expression and protein functions both in mitochondria and nuclei.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 HG-induced reactive oxygen/nitrogen species (ROS/RNS) overproduction may be a key event in activation of signaling pathways involved in the pathogenesis of atherosclerosis. 2,3 Interestingly, the mechanism of autoxidation describes the capability of glucose to enolize, thereby reducing molecular oxygen and yielding oxidizing intermediates, including superoxide anion (O 2 When macrophages respond to HG, ROS/RNS production was increased in cellular compartments and these reactive species triggered DNA strand breakage, leading to rapid increase in amounts of 8-hydroxydeoxyguanosine in DNA and decreases in the amount of DNA repair enzyme 8-oxoguanine glycosylase (OGG1). 2 Recent studies have revealed that HG-induced cellular changes lead to alterations of signal transduction cascades in macrophages, affecting gene expression and protein functions both in mitochondria and nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many studies have demonstrated that antioxidants and Akt/ERK1/2 inhibitors abolished HG-induced Akt/ERK1/2 expression in macrophages, thus implicating ROS/RNS and kinases as signaling molecules in this effect. 3,11 Ferenbach et al 12 demonstrated that resident kidney cells and infiltrating monocytes secreted the proinflammatory mediators such as cytokines, chemokines and growth factors in response to hyperglycemia. Recent publications have revealed that release of cytokines, including tumor necrosis factor-α (TNF-α)-, interleukin-6, and interleukin-1β due to hyperglycemia further aggravated the inflammatory infiltration and immune responses in the pathology of diabetic complications in macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, deletion or silencing of Nrf2 abolishes the antiatherogenic action of GYY4137 in diabetic mice and cells, illustrating the essential role of Nrf2. In addition, GYY4137 stimulates the expression of heme oxygenase 1 (HO-1) in an Nrf2-dependent manner, and depletion or inhibition of HO-1 abolishes the cellular actions of GYY4137, implicating HO-1 in the antiatherogenic effects of H 2 S. Notably, Xie et al (11) detect significantly lower levels of plasma H 2 S in diabetic mice that is corrected by the administration of GYY4137. A reduction in circulating H 2 S has also been noted in other diabetic animal models and patients with diabetes (7,(13)(14)(15), supporting the presence of an H 2 S deficiency state in diabetes.…”
mentioning
confidence: 99%
“…The study by Xie et al (11) represents an important advance in the field and identifies H 2 S as a novel therapeutic target in diabetes-accelerated atherosclerosis. The finding that Nrf2 functions as the initial transducer of the antiatherogenic action of H 2 S is somewhat surprising given the controversial role of Nrf2 in atherosclerosis (16), but it is in line with a recent report showing that Nrf2 activation represses atherosclerosis in a mouse model of diabetes (17).…”
mentioning
confidence: 99%